2018
DOI: 10.3389/fpls.2018.00725
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Tobacco GCN2 Stimulates Multiple Physiological Changes Associated With Stress Tolerance

Abstract: General control non-derepressible-2 (GCN2) is a ubiquitous protein kinase that phosphorylates the α subunit of the eukaryotic initiation factor, eIF2, preventing the initiation of a new cycle of protein synthesis, subsequently reducing the global protein biosynthesis. GCN2 can also regulate the response of plants to biotic and abiotic stresses. In this study, two GCN2 homologs, NtGCN2-1 and NtGCN2-2, were cloned from Nicotiana tabacum, and were predicted to have been derived from their progenitors in N. toment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…Altogether, the results indicate that GCN2 is involved in plant immunity against the necrotrophic fungus B. cinerea . These results are in accordance with the reduced induction of ET- and JA-related mRNAs in the gcn2 mutant analyzed by (Faus et al, 2015) and with the high production of MeJA and the lower accumulation of SA in the NtGCN2 overexpressing plants [ 14 ].…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…Altogether, the results indicate that GCN2 is involved in plant immunity against the necrotrophic fungus B. cinerea . These results are in accordance with the reduced induction of ET- and JA-related mRNAs in the gcn2 mutant analyzed by (Faus et al, 2015) and with the high production of MeJA and the lower accumulation of SA in the NtGCN2 overexpressing plants [ 14 ].…”
Section: Resultssupporting
confidence: 88%
“…Until now, different studies demonstrated that GCN2 is involved in eIF2α phosphorylation in response to other pathogens and to different phytohormones associated to plant immunity [ 7 , 14 , 15 ]. In this study, we report that GCN2 is also involved in plant defense against B. cinerea infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2b,c). Nevertheless, eIF2 alpha phosphorylation has been shown to take place in response to Pseudomonas syringae infection and upon infection by Bemisia tabaci (Li et al, 2018a;Pajerowska-Mukhtar et al, 2012) as well as in response to treatment with plant hormones involved in pathogen defence and the priming agent beta-aminobutyric acid (Lageix et al, 2008, Li et al, 2018a, Liu et al, 2015, Luna et al, 2014, Wang et al, 2017. Thus, additional studies are needed to clarify the specific function of eIF2 alpha phosphorylation upon biotic stress and to further define the conditions under which it is induced.…”
Section: Intracellular Recognition Of Dsrnamentioning
confidence: 99%
“…Even the stimulation of GCN2 by inhibitors of amino acid biosynthesis requires light and does not occur in darkness, suggesting that ROS are an essential requirement for GCN2 activation (Lokdarshi et al, 2020). A second conundrum surrounding plant GCN2 is that gcn2 mutants have rather mild phenotypes under favorable lab conditions (Liu et al, 2015b) and a near-normal transcriptome (Faus et al, 2015;Lokdarshi et al, 2020). Moreover, among the various treatments that activate eIF2α phosphorylation, the herbicide chlorosulfuron is the only one that also results in a GCN2-dependent global translational repression (Lageix et al, 2008;Lokdarshi et al, 2020).…”
Section: Introductionmentioning
confidence: 99%